Digital undergraduate medical education and patient and carer involvement: a rapid systematic review of current practice - Lawes-Wickwar, S; Lovat, E; Alao, A; Hamer-Hunt, J; Yurtoglu, N; Jensen, C; Clarke, N; Roberts, N; Park, S (BioMed Central, 2023)
Background: Involving patients and carers in medical students’ learning aims to centralise the perspective of healthcare users and supports our future medical workforce in the development of key skills. Medical schools are increasingly using digital technology for teaching and it is timely to understand how to maintain patient and carer involvement in this context.